INVESTMENT SERVICES: CIVIL LAW CHARACTERISATION OF THE RECEPTION, TRANSMISSION AND EXECUTION OF ORDERS - Didžiulis, Laurynas (Teisė, 2016)
The aim of this article is to identify the legal nature of classical investment services provided by the broker-dealers and to characterize these services in the light of a private law. In order to do this, author analyzed different sources of public and private law, which led to the conclusion that the legal relations of reception, transmission and execution of orders on behalf of investor in the Lithuanian private law should be characterized as agency relations. When financial intermediary acts on behalf of investor, but in his own name, as usually happens in the trading venues, agency relations are indirect, i.e. based on commission agency contract. In some over-the-counter transactions where financial intermediary acts in the name of and on behalf of investor, agency relations are direct, i.e. based of mandate contract. If, however, financial intermediary internalizes client’s order, technically it engages in the self-dealing and private law relations then are based on a principal counterparty trading, not an agency.